2022
DOI: 10.1038/s41598-022-11171-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of direct peptide reactivity assay for assessing the  skin sensitization potential of essential oils

Abstract: Plant-derived products are frequently found as ingredients in cosmetics. However, the current data show non-neglectable skin sensitizing potential of these preparations suggesting an urgent need for data regarding their health safety profile. The aim of this study was to assess the skin sensitization potential of commercial essential oils by selected Lamiaceae species (Lavandula angustifolia, Melissa officinalis, Mentha longifolia, Thymus vulgaris, Salvia officinalis, and Rosmarinus officinalis) using a chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Therefore, it is mandatory to ensure the increased quality of raw materials and extraction methods, in accordance with the provisions of European Pharmacopoeia, to ensure an appropriate safety profile of the cosmetic product [ 28 , 29 ]. EOs of the Lamiaceae family have the potential to sensitize and irritate the skin, causing allergic contact dermatitis and hypersensitivity reactions [ 30 ]. However, the use of EOs in topical preparations is generally safe, efficient, and less expensive when they are used in a decreased concentration or a diluted form, and the quality of the formulation is assured [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is mandatory to ensure the increased quality of raw materials and extraction methods, in accordance with the provisions of European Pharmacopoeia, to ensure an appropriate safety profile of the cosmetic product [ 28 , 29 ]. EOs of the Lamiaceae family have the potential to sensitize and irritate the skin, causing allergic contact dermatitis and hypersensitivity reactions [ 30 ]. However, the use of EOs in topical preparations is generally safe, efficient, and less expensive when they are used in a decreased concentration or a diluted form, and the quality of the formulation is assured [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…DPRA results confirmed that the skin sensitization potential is consistent with data available in the literature on this effect of essential oils. However, some discrepancies were noted when considering the phytochemical properties of the analyzed essential oils and the DPRA results, which further reinforces the need to use a combination of all methods that assess all three key events of the adverse skin sensitization outcome pathway in the assessment of skin sensitization (7). This extensive applicability highlights the DPRA's effectiveness in detecting skin sensitization hazards across diverse chemical categories.…”
Section: Direct Peptide Reactivity Assay Applicabilitymentioning
confidence: 87%
“…This interaction prompts the differentiation and proliferation of allergen-specific memory T-cells, marking the subsequent key event in the development of sensitization, an AO at the organ level. Once sensitized, an individual can mount a faster secondary response to the same chemical upon re-exposure, either at the same or a different skin site, leading to an aggressive immune response and resulting in allergic contact dermatitis (Figure 1) (7,8). The Direct Peptide Reactivity Assay (DPRA) method is closely linked to AOP40.…”
Section: Introduction Direct Peptide Reactivity Assay and Adverse Out...mentioning
confidence: 99%
“…Because of the strong irritant effect of EOs, the micellar encapsulation method was used in order to assure the safety of the product and to decrease the skin irritation caused by pure EOs [ 61 , 62 ]. For topical formulations based on polymeric micelles loaded with EOs, these concentrated multicomponent, hydrophobic liquid mixtures are encapsulated in the inner core of the micelles, thus being protected from degradation under different environmental conditions (e.g., temperature, light, pH, and oxygen) and promoting their penetration in and through the skin stratum corneum.…”
Section: Discussionmentioning
confidence: 99%